The Rohingya’s Muslim Asylum Seekers in Southeast Asia: From National to International Law Perspective - Khamami Zada (Universitas Islam Negeri Jakarta, 2017)
The Rohingya’s Muslim asylum seekers have recently been global issues. International, regional, and national law have provided legal basis that they have the right to look for asylum and to be protected. By normative and empiric approach, this study analyze the respect of Indonesian and Malaysian goverment to international, regional, and national law on refugees. This study found that both of Indonesian and Malaysian goverment have respected the international customary law, regional law, and national law that fulfill their rights to seek asylum, have agreed that they welcomed them and will take care of them. The implication is to protect them in some areas in these country.DOI: 10.15408/ajis.v17i1.6227